Perancangan dan Implementasi Router Mikrotik Pada Infrastruktur Jaringan Komputer Internet dengan Media Transmisi Wired dan Nirkabel (Studi Kasus : IAIN Curup) - Syahindra, Wandi (Arcitech: Journal of Computer Science and Artificial Intelligence, 2022)
This study aims to design, configure a proxy routerboard on internet computer network infrastructure with wired and wireless transmission media to overcome the uneven distribution of bandwidth to all internet users, inaccurate IP address addressing for each point of the building and wifi hotspot points, frequent network crashes, frequent slow internet access and many internet users install the netcut program with the aim of controlling network bandwidth, so that all bandwidth is fully absorbed so that other networks cannot receive bandwidth because the net cut program has taken over all bandwidth so internet access on other computers becomes very slow even disconnected. The method used is the method of analysis including surveys, interviews, identification of information needs. The design method includes making network topologies and determining resources. The analysis method is used to analyze the running system and the design method is used to create a network topology based on a proxy router. The result achieved is the design of an internet computer network infrastructure with wired and wireless media that has good management, bandwidth management and a good IP address address.